Length weight relationships of fish species collected after impoundment of the Three Gorges Reservoir (TGR) in China; a study carried out in the upper Yangtze River - H. A. C. C. Perera; Tanglin Zhang; Jing Yuan; Shawoen Ye; Chuanbo Guo; Jiashou Liu (Sri Lanka Journal of Aquatic Sciences, 2022)
The Three Gorges Dam in the upper Yangtze River in China is the largest hydropower project in the world. Length- weight relationships (LWRs) are reported for fish species collected from three locations of the reservoir from November 2010 to October 2011. Fish were collected from the local fishing boats using 1.5 cm nylon mesh trap nets or 4, 5 and 6 cm nylon mesh gillnets (100- 120 m long × 1.4-1.5 m high). A total of 7,311 fish representing 49 species of 11 families were collected during the study period. There were 2,680 fish belonging to 32 species of 8 families sampled in Zigui (near the dam) reach, 2,845 fish representing 46 species of 8 families in Wanzhou (middle of the reservoir) reach and 1,786 fishes representing 38 species of 8 families in Fuling (upper reservoir) reach. The family with the highest number of species was Xenocyprididae. The intercept (a) and slope (b) of LWRs are useful in fisheries science in many ways. Therefore, the present study provides baseline data on LWRs of the economically valuable and most abundant fish species in the recently commissioned Three Gorges Reservoir.